2013
DOI: 10.1007/978-88-470-5480-6_6
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Patient Mobility Across Italian Regions? Evidence from Hospital Discharge Data

Abstract: Patient mobility is often described as a marginal phenomenon in Europe since the overall number of patients that receive cross border care remains minor compared to the total population. However this phenomenon is increasing markedly. The process of globalization and the availability of medical information means that patients are more informed on treatment available well beyond their national boundaries. Patient empowerment implies that new generations will actively ask to be treated by the health care system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
0
29
0
1
Order By: Relevance
“…For patient characteristics, 10 out of the 17 studies that reported results demonstrated that older patients were more likely to receive treatment from their nearest hospital (Balia et al, 2014; Basu, 2005; Beckert et al, 2012; Beukers et al, 2014; Cook et al, 2009; Fattore et al, 2014; Hanning et al, 2012; Howard, 2006; Roh & Moon, 2005; Varkevisser & van der Geest, 2007). Six out of nine studies demonstrated that patients in lower socioeconomic groups were more likely to receive treatment from their nearest providers (Beckert et al, 2012; Cook et al, 2009; Howard, 2006; Losina et al, 2007; Varkevisser et al, 2010; Varkevisser & van der Geest, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For patient characteristics, 10 out of the 17 studies that reported results demonstrated that older patients were more likely to receive treatment from their nearest hospital (Balia et al, 2014; Basu, 2005; Beckert et al, 2012; Beukers et al, 2014; Cook et al, 2009; Fattore et al, 2014; Hanning et al, 2012; Howard, 2006; Roh & Moon, 2005; Varkevisser & van der Geest, 2007). Six out of nine studies demonstrated that patients in lower socioeconomic groups were more likely to receive treatment from their nearest providers (Beckert et al, 2012; Cook et al, 2009; Howard, 2006; Losina et al, 2007; Varkevisser et al, 2010; Varkevisser & van der Geest, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Different measures of provider quality were used in each of the studies (e.g., generic mortality rates, hospital infection rates, heart failure readmission rates, transplant failure rates, high volume surgical unit, hospital ranking). Other provider factors that are associated with a willingness to travel further are the availability of advanced technology (although not necessarily for the specialty in question) and a larger hospital (Balia et al, 2014; Escarce & Kapur, 2009; Fabbri & Robone, 2010; Ho, 2006; Roh & Moon, 2005). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, if patients are free to choose the health care provider, expected satisfaction drives the individual choices about the provider, and patient mobility has to be expected. Patient mobility—both across the regions of any given country and even across countries—is a widely observed phenomenon indeed (see, e.g., Rosenmoller, McKee, & Baeten, ; Balia, Brau, & Marroccu, ); the phenomenon is expected to increase in next future, at least in the European Union in front of recent directives. This mobility, per se, is not a negative by‐product of the system; it associates with the aim of stimulating competition and increasing quality.…”
Section: Introductionmentioning
confidence: 99%
“…Patients can choose any public or privately accredited facility in the country: mobility is in fact allowed not only across LHAs but also across Regions. The empirical evidence shows that interregional mobility involves a non-negligible share of patients and concentrates mainly on highly specialised treatments (Fabbri and Robone, 2010;Balia et al, 2014) Moreover, differences in waiting times for eligible treatments together with free patients' mobility generate incentives to shop around in search of faster responses not only for outpatient but also for inpatient services (Fattore et al, 2013).…”
Section: Institutional Settingmentioning
confidence: 99%